Analisis Nilai Tambah Produk Gula Cair di PT Gula Energi Nusantara Semarang - Atqiya, Muhammad Wildanul; Handayani, Migie; Budiraharjo, Kustopo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Sugar is one of the important and strategic commodities for the community. One of the sugars that are often used by the community is granulated sugar. The use of granulated sugar as a raw material for beverages has received unrest in the community in the form of high economic costs and a high risk of developing diabetes. PT Gula Energi Nusantara Semarang sees the potential of the granulated sugar industry that can be given added value through the manufacture of liquid sugar and low glycemic index (LGI) liquid sugar. This research aims to analyze the added value and profitability of liquid sugar products at PT Gula Energi Nusantara Semarang. The research method used is the case study method. The analysis method used is the Hayami Method to calculate the added value of liquid sugar and the one sample t-Test method to calculate profitability. The added value of liquid sugar products at PT Gula Energi Nusantara Semarang is divided into two, namely original liquid sugar and LGI. The added value of original liquid sugar amounted to IDR5,445.00 and the value-added ratio was 33.51% and classified as medium category. The added value of LGI liquid sugar is IDR 7,945.00 and the added value ratio is 43.37% and is classified as a high category. The average profitability value in 2023 is 24.71% and higher than the BRI deposit interest rate as of 2023 which is 4.00%. This value means that there is a significant difference between profitability and bank interest rates, so the liquid sugar production business is profitable.